Woman at the Ball. “Anna on the Neck” by Anton Chekhov and “The Psychology of a Husband from Syros” by Emmanuel Roidis: An Attempt of Comparison - Eloeva, Fatima (Literatūra, 2021)
The paper presents the first attempt to compare two short stories – Anna in the Neck by Anton Chekhov and a well-known short story by the Greek author Emmanuel Roidis Psychology of a Husband from Syros. Both texts were published at the same time (in 1895) and are considered to be masterpieces. The initial motivation for such textual analysis became almost a complete coincidence between the plots of the two stories. A series of telling coincidences and contradictions observed between the analyzed stories require some kind of explanation which will allow us to view both texts from the different angle. The paper aims to determine the correlation between the writers’ biographies and the personality traits with the characteristics of the protagonists and the style of story telling.
Keywords: Anton Chehkhov; Emmanouel Roidis; fabula; plot; style of story telling; ball scene in the fiction of the XIX c.